Weigth of africanized virgen queens produced in colonies under diferents food supplementation at Mossoró-RN, Brazil - Pereira, Daniel Santiago (2015)
The aim of this study was to evaluate whether there are differences in birth weight of queen bees produced in mini recreating fed three different formulations of feed protein. The experiment was conducted during the period June to August 2011 at the experimental farm Rafael Fernandes, "Campus" Federal Rural University of the Semi-Arid - UFERSA Mossoró / Rio Grande Norte - Brazil. We used six hives with swarms mini recreating assets and populated, for the production of queens method was used to Doolittle (1899), using acrylic domes yellow. The treatments were: T1 - 40% soy, 60% sugar, vanilla essence, T2 - 40% soy, 10% honey, 50% sugar, 10% T3-pollen, 30% soy, 10% honey, 50% sugar. The six mini recreating fed fifteen days before the transfer of larvae to T1 adjusted each food was provided 400g of feed, and repeated on the day of receipt of cups. Queen cells collected were placed in BOD, and heavy queens in the first 10 hours of life. Data were statistically analyzed by using the program Statistical Package for Social Science (SPSS), version 17.0 (SPSS. Inc, Chicargo, IL, USA) and expressed as mean and standard deviation, subjected to analysis and test of normality Mann-Whitney test. P values <0.05 were considered significant. Performed the ANOVA showed that there was no statistical difference between treatments (p <0.05). The weight of the queens for each treatment was T1 - 172.95 ± 29.22b; 177.46 ± 27.81ab-T2, and T3 - 183.03 ± 31.10a. Food with pollen proved to be more effective in producing queens with weight exceeding 180 mg.